2021
DOI: 10.11604/pamj.2021.40.203.28804
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus type 16 (HPV-16) IgG antibody among women of reproductive age presenting at a healthcare facility in Central Nigeria: a pilot study

Abstract: Approximately, 70% of cervical cancer cases worldwide are attributable to HPV-16 and HPV-18, with HPV-associated cancers being the second most common infection-related cancers globally. However, there´s paucity of data about this infective agent in Central Nigeria. In a cross-sectional study, we evaluated the seroprevalence of HPV-16 immunoglobulin G (IgG) and risk determinants among women in Central Nigeria as a first step towards evaluating anti-HPV IgM antibody for active cases and determining incidence. Bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The microtiter plate provided in the ELISA kit (Cusabio Co Ltd., Germany) was pre-coated with an antigen specific to detect the HPV-16 IgG antibody in the participantsʼ sera samples. In accordance with manufacturerʼs specifications, the test procedure was conducted and the results were interpreted based on previous protocol 10,12 . The intensity of colour change was measured spectrophotometrically at 450 nm using an ELISA reader (Tecan Group Ltd., Mannedorf, Switzerland).…”
Section: Hpv-16 Detection By Elisamentioning
confidence: 99%
“…The microtiter plate provided in the ELISA kit (Cusabio Co Ltd., Germany) was pre-coated with an antigen specific to detect the HPV-16 IgG antibody in the participantsʼ sera samples. In accordance with manufacturerʼs specifications, the test procedure was conducted and the results were interpreted based on previous protocol 10,12 . The intensity of colour change was measured spectrophotometrically at 450 nm using an ELISA reader (Tecan Group Ltd., Mannedorf, Switzerland).…”
Section: Hpv-16 Detection By Elisamentioning
confidence: 99%
“…The Republic of Congo has a reported prevalence of 23.5%, Burkina Faso has 25.4%, Benin Republic has 33.2% Rwanda has 34%, respectively (13,14,15,16). Diverse prevalence has also been reported by studies across some states in Nigeria which include studies in Kano State (17), Nasarawa (18), Osun (3), Lagos (19), Adamawa (20), Rivers (21) (26). The methods used to detect HPV in most studies contributed to the differences in prevalence observed.…”
Section: Introductionmentioning
confidence: 99%